Comparison of GentleWave system and passive ultrasonic irrigation with minimally invasive and conventional instrumentation against LPS in infected root canals - Velardi, Johnathan P.; Alquria, Theeb A.; Alfirdous, Rayyan A.; Corazza, Bruna J. M. [UNESP]; Gomes, Ana P. M. [UNESP]; Silva, Eduardo G. [UNESP]; Griffin, Ina L.; Tordik, Patricia A.; Martinho, Frederico C. (Springer Nature, 2022)
This study compared the effectiveness of GentleWave system (GWS) and passive ultrasonic irrigation (PUI) in removing lipopolysaccharides (LPS) from infected root canals after minimally invasive (MIT) and conventional instrumentation (CIT) techniques. Sixty first premolars with two roots were inoculated with fluorescent LPS conjugate (Alexa Fluor 594). Of those, twelve were dentin pretreated, inoculated with fluorescent LPS conjugate, and submitted to confocal laser scanning microscopy (CLSM) to validate the LPS-infection model. Forty-eight teeth were randomly divided into treatment groups: GWS + MIT, GWS + CIT, PUI + MIT, and PUI + CIT (all, n = 12). Teeth were instrumented with Vortex Blue rotary file size 15/0.04 for MIT and 35/0.04 for CIT. Samples were collected before (s1) and after a root canal procedure (s2) and after cryogenically ground the teeth (s3) for intraradicular LPS analysis. LPS were quantified with LAL assay (KQCL test). GWS + MIT and GWS + CIT were the most effective protocols against LPS, with no difference between them (p > 0.05). PUI + CIT was more effective than PUI + MIT (p < 0.05) but less effective than GWS + MIT and GWS + CIT. GWS was the most effective protocol against LPS in infected root canals using MIT and CIT techniques.